1994
DOI: 10.2186/jjps.38.476
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Occlusal Support in the Elderly.

Abstract: The distribution of occlusal support of 366 aged patients of over 70 years was surveyed and analyzed in this study. Their masticatory abilities were also evaluated by the questionnaire on the masticatory aspects of 20 kinds of foods, and their maximum occlusal forces were measured with the pressure sensitive foil. The relations among masticatory ability, maximum occlusal forces and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…First, in a previous modification of the EI, removable dentures were evaluated. However, in a 1993 study of occlusal support in the elderly, Suzuki reported that removable dentures could not provide sufficient occlusal support 11 . In addition, in 1980, Miyata et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in a previous modification of the EI, removable dentures were evaluated. However, in a 1993 study of occlusal support in the elderly, Suzuki reported that removable dentures could not provide sufficient occlusal support 11 . In addition, in 1980, Miyata et al .…”
Section: Discussionmentioning
confidence: 99%
“…It indicates whether the existing teeth form occlusal support zones, specifically whether there is existing natural tooth contact between the maxilla and mandible in the bilateral premolar and molar regions. Recent research has shown that EI in elderly people is associated with occlusal force and masticatory performance 11–16 . However, according to the 2005 Survey of Dental Diseases by the Ministry of Health, Labour and Welfare, with aging the number of existing teeth decreases, and that of artificial teeth increases.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that the number of remaining teeth is related to the efficiency of mastication (Mumma and Quinton, 1970;Chen and Lowenstein, 1984;Ando et al, 2000;Suzuki et al, 1993;Maeda et al, 1996). The loss of teeth leads to decreased food intake, particularly the intake of dietary fiber and vitamin C (Sheiham and Steel, 2001), due to difficulty with mastication and swallowing.…”
Section: Introductionmentioning
confidence: 99%